G241(P) Echocardiograms in children – a parental perspective. (27th April 2015) - Ranaweera, M; Venugopalan, P
Abstract : Introduction and aim: Cardiac murmurs are reported in 50–90% of children at some time in their life, but only 1% are pathological. It is widely questioned whether performing echocardiograms on these children with asymptomatic murmurs is cost-effective or not. We designed this study to survey parents of children who had echocardiograms for asymptomatic heart murmurs which then proved to be benign. Methods: All new referrals for 'asymptomatic heart murmurs' to the paediatric cardiac clinic, run by a paediatrician with cardiology expertise, over a one-year period were reviewed. The parents of children with normal echocardiograms were requested to answer a questionnaire that elicited their experience of the echocardiogram and its impact on their concerns. Permission for this study was obtained, and consent sought from contacted parents. Results: 166 new patients attended the clinic during the study period, 67/166 were for asymptomatic heart murmurs. 58/67 of these patients had normal echoes. Among the 58patients, 51 were contacted by telephone for the survey (Table 1 ). None of these children had any repeat consultations for the murmur, and parents were convinced that the echo gave them the reassurance that they badly needed. Conclusions: Our study concluded echocardiograms provide parents with a satisfactory conclusion to the consultation. This may be a cost-effective method in reducing repeat consultations for the same concerns.